Hirayama Disease (Monomelic Amyotrophy) - Gokhan Alkan; Gurkan Akgol; Arif Gulkesen; Arzu Kaya (Medicine Science, 2017)
Hirayama disease (HD) or monomelic amyotrophy (MA) is a rare muscular atrophy that affects young Asian males, usually occurs in one of the upper limbs that progresses slowly. It is diagnosed by means of electromyographic/electroneurographic conduction speed studies and by magnetic resonance imaging (MRI) of the spinal cord. In this paper two different HD case is reported. [Med-Science 2017; 6(3.000): 560-1]